2018
DOI: 10.1111/bju.14410
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of treatment success after collagenase Clostridium histolyticum injection for Peyronie's disease: development of a nomogram from a multicentre single‐arm, non‐placebo controlled clinical study

Abstract: Patients with longer PD duration, greater baseline PC and basal plaque location had a greater chance of treatment success. These results could be applied to clinical practice before external validation of our nomogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…This condition can lead to penile curvature, painful erections and erectile dysfunction (ED). PD is believed to affect 3% to 9% of the male population, with a higher prevalence among patients suffering from ED, diabetes and cardiovascular disease [1][2][3][4]. PD presents 2 different phases: active or acute and stable or chronic.…”
Section: Introductionmentioning
confidence: 99%
“…This condition can lead to penile curvature, painful erections and erectile dysfunction (ED). PD is believed to affect 3% to 9% of the male population, with a higher prevalence among patients suffering from ED, diabetes and cardiovascular disease [1][2][3][4]. PD presents 2 different phases: active or acute and stable or chronic.…”
Section: Introductionmentioning
confidence: 99%
“…The CCH protocol used in the present study has already proven its usefulness as an alternative to the IMPRESS protocol in a first report of results [12]. That first study showed that the decrease in curvature per cycle (two injections of 0.9 mg) was 14 (11)(12)(13)(14)(15)(16)(17)(18)(19)°, which corresponds to a 26% decrease in curvature. The IMPRESS studies [7] showed an improvement after four cycles (eight injections) of 34% (17°).…”
Section: Discussionmentioning
confidence: 72%
“…It has been found to degrade type I and III collagen selectively, which are the predominant forms in Peyronie's plaque tissue . Since its approval, some modifications of the original protocol of drug use – adding vacuum therapy, shortening the protocol or increasing the dose of each injection – have been suggested to optimize treatment outcomes and reduce costs , and predictive factors have also been evaluated to provide better selection of patients for this therapy .…”
Section: Introductionmentioning
confidence: 99%
“…CCH is one of the newest nonsurgical options that appeared on the market, and to date is the only licensed drug for this disease (European Medicines Agency, ). Its safety and efficacy have already been demonstrated in two large RCTs, various retrospective studies, and some authors have also tried to identify predictors of treatment success (Cocci, Russo, Briganti, et al, ; Cocci, Russo, Salonia, et al, ; Gelbard et al, ; Lipshultz et al, ). A standardised protocol of injections has not been established yet, considering that the modified shortened protocol (three injections) has given comparable results to the initial IMPRESS protocol (eight injections; Abdel Raheem, Capece, et al, ; Abdel Raheem, Johnson, et al, ; Capece et al, ).…”
Section: Discussionmentioning
confidence: 99%